Proposed campus landscape design for fsa admininstration building - Pang, Qi Wei (Universiti Malaysia Sabah, 2018)
This study aims to propose the restorative landscape in campus for restoration capacity of student's attention and being healthy. The objectives of this study are to conduct site inventory and analysis at proposed site; to propose restorative landscape design by using tropical plant material for the site of administration building area and to conduct questionnaire survey to gain feedback on the landscape design from the stakeholders. The data collection will be 1. Questionnaire survey 2. Descriptive statistical analysis 3. Landscape design recommendation, which get the feedback from stakeholder. These data collection involved the participation of 60 students in campus. Based on the findings, the existing landscape at Administration Building of Faculty Sustainable Agriculture can be improved to offer aesthetic view and restorative landscape in campus for reducing tension from academic activities. The proposed site was divided into four zones namely Zone A, Zone B, Zone C and Zone D. Master plan, perspective views of zones and planting material were produced in landscape design recommendation alter data collection of study. In conclusion, the vegetation and water bodies could promote a sense of being away from daily workout.